Glocalization Of Tourism Attractions In The Kuta Area Of Bali - I Ketut Surata (Journal Of Social Science (JoSS), 2024)
This study examines the process of glocalization in the tourism industry in Kuta, Bali, with a particular focus on tourist attractions. This research explores how local culture has been transformed into a marketable commodity to meet the demand of global tourists. Through the lens of Commodification, the study analyzes how traditional Balinese elements, such as rituals and architecture, have been integrated into the tourism landscape. This research is a qualitative research method that uses observation, document analysis, and interviews as data collection techniques. The study shows how Kuta has achieved a delicate balance between global appeal and local authenticity through a detailed analysis of various case studies, including Waterboom Park and the integration of traditional Balinese rituals into tourism activities. By examining the interaction between global market forces and local cultural practices, the study offers insights into the complexity of cultural tourism and its impact on host communities. These findings highlight the importance of glocalization in the tourism industry and provide valuable insights for destination management and development.